Melek Information and Communications Technology (ICT) Pada Masyarakat Pedesaan Di Era Globalisasi - Anggun Tri Kurniawatik; Khaerunnisa Khaerunnisa; Tasya Tasya (IHSA Institute, 2021)
The development of information and communication technology is one form of the presence of the era of globalization. The faster the development, the easier it is for someone to access information. However, the inequality of technological developments can be felt in places where internet access is difficult, such as in Ciakar Village. With descriptive quantitative research, this research can see the views of the people of Ciakar Village in facing the development of information and communication technology. The development of ICT is currently needed not only in the city but in the village as well, because ICT literacy provides many benefits both in the economic, social, cultural, political and so on. So that the development of ICT, it must be felt evenly to find out how the conditions are happening in our country.